MicroRNAs in cancer therapeutics: “from the bench to the bedside” - Monroig-Bosque, Paloma del C. (Expert Opin Biol Ther, 2015)
MicroRNAs (miRNAs) are non-coding RNA transcripts that regulate physiological processes by targeting proteins directly. Their involvement in research has been robust, and evidence of their regulative functions has granted them the title: master regulators of the human genome. In cancer, they have been considered important therapeutic agents, due to the fact that their aberrant expression contributes to disease development, progression, metastasis, therapeutic response and patient overall survival. This has endeavored fields of biomedical sciences to invest in developing and exploiting miRNA-based therapeutics thoroughly. Herein we highlight relevant ongoing/open clinical trials involving miRNAs and cancer.